The Ectoparasites Inventory on Cultured Carp in Floating Cage Net at Laut Tawar Lake Kabupaten Aceh Tengah - Winaruddin W; Eliawardani E (Universitas Syiah Kuala, 2007)
The aimed of this research is inventoried the parasites of carp in floating cage net at Laut TawarLake. This study used 100 fishes consisted of 50 fries and 50 reproductive stadia. The result of thisresearch indicates the parasites found in the fishes are Trichodina sp., Ichtyophthirius multifiliis,Dactylogyrus sp., Gyrodactylus sp., Epistylis sp. and Lernaea sp. Protozoan parasites were found in allfishes and infected fish organs, while metazoan parasites infected fins and gills and copepods only infectedskin.Keywords: parasites, carps, floating cage net, Laut Tawar Lake